An in-Depth Exploration of EFL Teachers’ Grammar Teaching Cognition - Setoodeh, Khalegh; Jadidi, Esmaeil (International Journal of Language Education, 2020)
L2 research, during the last two decades, has almost abandoned studying appropriacy of methodologies and techniques to focus more on the underlying derives for teachers’ pedagogical decision makings inside the class. Borg’s (2003) ideas of the role of teachers’ cognition in their adaptation and adoptation of teaching techniques and activities have noticeably influenced L2 professional research community. This study, in line with the recent trend, is designed and conducted to elicit EFL teachers’ grammar teaching cognition to have more comprehensive accounts of teachers’ behaviors in the class. In so doing, a Likert scale 25-item questionnaire developed by Naashia (2006) was administered to 177 Iranian EFL teachers. The results indicated that EFL teachers are currently more inclined toward communicative focus on grammar in which grammar instruction is marginalized to have learners naturally act out linguistics rules while performing communicative tasks.